Edukasi Penerapan Teknologi Bioflok pada Kelompok Pembudidaya Lele di Desa Tengket Arosbaya - Qomariyah, Nor; Triyasari, Sri Ratna; Yunia Sari, Riska Ayu (Jurnal Ilmiah Pangabdhi, 2024)
This article contains a communication strategy for activities socializing cultivation of catfish by using bioflock system on the Jaya Lestari fish farming group, Tengket Village Arosbaya District. Tengket Village has great potential in the field of fisheries where the majority of the people are fishermen. The market demand for catfish is still very high. but has not been able to supply the needs of catfish continuously every day, due to limited land and capital owned. One way that can be done is the cultivation of catfish by using bioflock system. The introduction of bioflock system on fish farming cultivation of "Jaya Lestari" fish farming group was conducted on October 25, 2022. The socialization was conduct by presenting the material first, then followed by a discussion or question and answer session. The results of this activity indicate that the introduction of bioflock system on the cultivation of catfish in the fish farming group "Jaya Lestari" has been running very well, seen from the enthusiasm of the group to immediately apply the bioflock system on their catfish cultivation business. This is the result of the communication strategy implemented in the socialization activity of the cultivation of catfish by using bioflock system.